Immobilization and Evaluation of Penicillin G Acylase on Hydroxy and Aldehyde Functionalized Magnetic α-Fe2O3/Fe3O4 Heterostructure Nanosheets - Ni, Yun; Lv, Zhixiang; Wang, Zhou; Kang, Shouyu; He, Dawei; Liu, Ruijiang (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic α-Fe2O3/Fe3O4 heterostructure nanosheets were fabricated via hydrothermal calcination. The activity of penicillin G acylase (PGA), which was covalently immobilized onto silica-decorated heterostructure nanosheets, achieved the highest activity of 387.03 IU/g after 18 h of incubation with 0.1 ml of PGA. In contrast, the activity of free PGA reached the highest level when the temperature was 45°C with a pH of 8.0. However, the activity of free PGA changed more dramatically than immobilized PGA as the relative conditions changed. Moreover, the Michaelis–Menten constant (Km) and reusability of immobilized PGA were also explored. The results showed that free PGA Km and maximum rate (Vmax) were 0.0274 M and 1.167 μl/min, respectively. Km and Vmax values of immobilized PGA were 0.1082 M and 1.294 μl/min, respectively. After 12 cycles of repetitive use, immobilized PGA remained approximately 66% of its initial activity, indicating that the PGA immobilized onto the heterostructure nanosheets showed better stability and reusability than free PGA.